Game Theory - Peters, Hans (Springer, 2015)
This book is a compilation of much of the material I used for various game theory courses over the past decades. The first part, Thinking Strategically, is intended for undergraduate students in economics or business, but can also serve as an introduction for the subsequent parts of the book. The second and third parts go deeper into the various topics treated in the first part. These parts are intended for more mathematically oriented undergraduate students, or for graduate students in (for instance) economics. Part II is on noncooperative games and Part III on cooperative games. Part IV consists of a mathematical tools chapter, a chapter with review problems for Part I, and a chapter with hints and solutions to the problems of all chapters. Every chapter has a section with problems. Thematerial draws heavily on game theory texts developed by many others, often in collaboration. I mention in particular Jean Derks, Thijs Jansen, Andrés Perea, Ton Storcken, Frank Thuijsman, Stef Tijs, Dries Vermeulen, and Koos Vrieze. I am also seriously indebted to a large number of introductory, intermediate, and advanced texts and textbooks on game theory, and hope I have succeeded in giving sufficient credits to the authors of these works in all due places.
A Multi-Leveled Approach